The Impact Of The Strategy Of The Five-Year Learning Cycle In The Achievement Of Fourth-Grade Students In The Subject Of Arabic Grammar And The Development Of Their Literary Trends - Salman Al Nuaimi, Mohsen Mouloud (Opción, 2019)
The objective of the current research is to identify the impact of the five-year learning strategy in the achievement of fourth grade students in the Arabic grammar and the development of their literary trends. The sample consisted of (50) students, randomly distributed to two groups, one experimental and the other an officer. The researcher used many statistical methods such as T-test for two independent samples, which resulted in the superiority of the students of the experimental group on the students of the group of officers In the achievement test and in the measure of literary trends, and the researcher came out with some conclusions, recommendations and suggestions.